Simulation du travail en formation : constructivisme, intentions didactiques et mannequins en maïeutique - Lucile Vadcard; Christian Dépret; Vasiliki Markaki-Lothe (Éducation et Socialisation)
Simulation is now widely used in professional health training. These material devices make it possible to mobilize work situations for training. However, they are based on a presupposition that is rarely addressed, which consists in thinking that reality can be grasped in a univocal and easy way by all, and that it allows to build shared knowledge. In this text, we study a situation of practical work on a mannequin in midwifery. We propose four categories of analysis that allow us to grasp the complexity of the didactic interactions that take place between the teacher and the students: in a simulation situation, what must be perceived, and what must not be perceived, is not obvious and the teacher's guidance work is absolutely central.